Effect of Mineral Sulfur on the Intensity and Capacity Relationship of Copper in Different Calcareous Soils - Hamad, Zakia Shihab; Al-Jumaily, Mijbil M.; Mahmoud, Asmaa Sami; Mohammed, Rusul Jamal; Ghafel, Noor Ammar (American Journal of Botany and Bioengineering, 2026)
The study aims to evaluate the effect of mineral sulfur on the availability of copper in different calcareous soils by adopting some thermodynamic parameters (capacity and intensity relationships, free energy, Gabon’s constant). Three levels of mineral sulfur (1,2,3) g.kg-1 were adopted. The study showed that the coefficient of statistical determination of the amplitude and intensity equations ranged between (0.82 and 0.99), and the values of the regulatory capacity ranged between (282.58, 574.76) (centimol.kg-1), while the values of mobile copper CU-Labile ranged between (0.0093-0.0093). The values of free energy (15.7865, 26.7014) kilojoules.mol-1, while the values of the preference coefficient for Gabon ranged (12.7288, 40.2459). These results indicate that all thermodynamic values decrease (increase in copper availability) with increasing levels of added mineral sulfur (1,2,3) g.kg-1 in the soil.